2017
DOI: 10.3892/ol.2017.7043
|View full text |Cite
|
Sign up to set email alerts
|

Riparsaponin isolated from Homonoia?riparia Lour induces apoptosis of oral cancer cells

Abstract: Abstract. Homonoia riparia Lour (Euphorbiaceae) is a known source of herbal medicine in China, and riparsaponin (RSP) is an active constituent isolated from H. riparia. The aim of the present study was to investigate the antitumor effect of RSP on human oral carcinoma cells and its potential underlying molecular mechanism. RSP was isolated from roots of H. riparia and identified using nuclear magnetic resonance. An MTT assay was used to evaluate the cytotoxicity of RSP on human oral carcinoma cells. Subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Staining treated cancer cells and their examination via fluorescent microscopy are considered as acceptable methods for the evaluation of morphological changes as well as cytotoxicity expression in the chromatin and cell membrane (Li & Wang et al., 2017). The DAPI staining method was engaged to detect the phenotypic sign of apoptosis in treated cancerous cells.…”
Section: Resultsmentioning
confidence: 99%
“…Staining treated cancer cells and their examination via fluorescent microscopy are considered as acceptable methods for the evaluation of morphological changes as well as cytotoxicity expression in the chromatin and cell membrane (Li & Wang et al., 2017). The DAPI staining method was engaged to detect the phenotypic sign of apoptosis in treated cancerous cells.…”
Section: Resultsmentioning
confidence: 99%
“…HIF-1α is hydroxylated by prolyl hydroxylase under conditions of sufficient oxygen, leading to its degradation. However, under hypoxic conditions, the HIF-1α protein is stabilized and accumulates due to inhibition of prolyl hydroxylase ( 26 ). The hydroxylation of prolyl hydroxylase requires molecular oxygen, and cobalt can replace the ferrous ions bound to the active site, causing the inactivation of hydroxylase, thereby stabilizing the HIF-1α protein, and this has been widely used to simulate hypoxia in vitro ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cytochrome c is an initiator of apoptosis, and is primarily associated with the Bcl-2 family of proteins, such as Bax and Bcl-2. Bax promotes the release of cytochrome c from the mitochondria, thereby activating a series of downstream caspase reactions leading to apoptosis, whereas Bcl-2 prevents the release of cytochrome C by maintaining the integrity of the mitochondrial membrane ( 26 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ginsenoside M1 (64) dose-dependently inhibits the colony formation and migration of SAS and OEC-M1 cells and reduces the expression of the transfer-related protein vimentin. Li et al [100] found that riparsaponin (65) inhibits OSCC metastasis by down-regulating the expression of cellular-mesenchymal epithelial transition factor (c-MET), MMP-2, and MMP-9 and by up-regulating the expression of E-cadherin; it also shows significant anti-OSCC activity by inducing mitochondria-mediated apoptosis. Gambogic acid causes the G1 arrest of OSCC cells.…”
Section: Terpenoids and Steroidsmentioning
confidence: 99%